ANALISIS PENGARUH DANA ZAKAT PRODUKTIF DALAM PEMBERDAYAAN DAN PERKEMBANGAN USAHA MIKRO MUSTAHIK (PENERIMA ZAKAT) DI KOTA SEMARANG - novia budiawati (Diponegoro Journal of Islamic Economics and Business, 2025)
In an effort to improve the standard of living and welfare of the people in a country, one of the efforts that must be made by the government is to increase economic growth. One of the efforts made by the government to achieve this goal is a community empowerment program through the provision of productive zakat funding assistance to Micro, Small and Medium Enterprises (MSMEs). This study aims to find out the effect of productive zakat funding assistance provided by BAZNAS Central Java on development micro business for mustahik zakat recipients. This research uses descriptive analysis method and Wilcoxon Signed Rank Different Test where the number of samples used is 50 respondents. This study aims to determine the effect of productive zakat on business capital, business income, business profits, and household expensesKeywords:  Productive Zakat; Zakat Fund Assiitance; Business Capital; Business Income; Business Benefits; Houshold Expenditures